Mining and analysis of adverse event signals of isotretinoin based on the real-world data of FAERS database - Yang, Liu; Xie, Hanzhang; Jia, Ying; Cui, Bingnan; Xiao, Zhanshuo (Frontiers in Medicine, 2025)
ObjectiveIsotretinoin (ISO) is an oral prescription retinoid that is well-known for its effectiveness in treating acne. This study aims to provide valuable insights into the safety of its clinical use by analyzing adverse events (AEs) associated with ISO reported in the FDA Adverse Event Reporting System (FAERS) database.MethodsFAERS data from Q1 2004 to Q2 2024 were analyzed. Duplicate reports were excluded, and disproportionality analysis using four algorithms (ROR, PRR, BCPNN, EBGM) was performed. AEs were classified using MedDRA terms, with Important Medical Events (IMEs) flagged based on the MedDRA IME list.ResultsThe FAERS database identified 46,526 ISO-related AE reports covering 27 System Organ Classes (SOCs). Of these, 445 AEs showed significant signals across all four algorithms, including 38 previously unlabeled AEs within the top 50 positive Preferred Term (PT) signals. Key IMEs, such as Dandy-Walker syndrome (N = 13), childhood depression (N = 3), and suicidal ideation (N = 2,175), were identified, with Gastrointestinal Disorders being the most frequently reported SOC (10,064 reports). AEs occurred most frequently in the early (0–30 days, 23.5%) and mid-treatment phases (91–180 days, 22.7%), with females accounting for 55.9% of the reports.ConclusionThis study identified previously unlabeled AEs and IMEs associated with ISO, including life-threatening events such as Dandy-Walker syndrome, suicidal ideation, and childhood depression, emphasizing the need for updated drug labels and enhanced safety measures. Future research should focus on mechanisms underlying teratogenicity and psychiatric risks to refine ISO’s safety profile.